POST-SOVIET INTEGRATION THROUGH THE PRISM OF POLITICAL TRANSFORMATION IN THE NEWLY INDEPENDENT STATES - SAFAEVA, Saida (CENTRAL ASIA AND THE CAUCASUS, 2007)
The integration processes in the republics that acquired their sovereignty after the collapse of the Soviet Union naturally became one of the main elements in the widespread transformation process going on in the geographical expanse now known as post-Soviet. This is turning regional integration into one of the most urgent problems in the study of the new processes and phenomena occurring in this region.Indeed, if integration is to be successful, we will be dealing with an essentially new type of unification, that is, reintegration. If it fails, the united expanse will continue to disintegrate, whereby completely.At the current stage, it is still impossible to draw foregone conclusions and make predictions about either the first or the second scenario. Both integration and disintegration processes are going on at the same time with different degrees of intensity in the so-called newly independent states (NIS).Of particular interest is the Central Asian region, where the local, post-Soviet, and international factors influencing the political transformation of the NIS and, consequently, the nature of their partic ipation in the integration processes are concentrated. In turn, interpretation of the vitally important question for the NIS—what does sovereignty mean for them?—depends on this. However, this question is pertinent and just as significant for all the NIS in the post-Soviet expanse. So it is extremely important to study their political transformation and the effect this process is having on the fate of NIS integration. Ultimately, political transformation affects the nature of the integration processes and vice versa—the integration processes are influencing the nature of political transformation in the NIS.From the very beginning of the era of independence, political science studies of the NIS invariably concentrated on the idea of post-Soviet reintegration. Many experts have studied the Commonwealth of Independent States (CIS), which arose in place of the disintegrated U.S.S.R. Almost all the former Soviet logical centers in the West have switched to CIS topics.On the other hand, today, in the era of globalization, the phenomenon of regional integration unions is a graphic trend in international relations. There are many relevant examples: the EU, ASEAN, NAFTA, MERCOSUR, the UAE, and others. The NIS of the post-Soviet expanse face the same historical challenge, meaning “is integration to be or not to be?” This does not simply entail a review of interrelations, it is also a question of the place and destiny of these states in the globalizing world order.